1970
DOI: 10.1103/physreva.2.256
|View full text |Cite
|
Sign up to set email alerts
|

Speculations on Bose-Einstein Condensation and Quantum Crystals

Abstract: It is shown, by almost rigorous arguments, that there exist many-body states of a system of interacting bosons which exhibit both crystalline order and Bose-Einstein condensation into the zero-momentuxn eigenstate of the single-particle density matrix. The implications of this result are discussed in relation to theories of superfluidity and the nature of quantum crystals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
714
0
17

Year Published

1977
1977
2013
2013

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 592 publications
(751 citation statements)
references
References 4 publications
20
714
0
17
Order By: Relevance
“…The existence of an exotic supersolid crystalline phase with combined solid and superfluid characteristics has been long conjectured 16,17,18 for solid 4 He under appropriate conditions. The recent experimental discovery 19 that solid 4 He exhibits a nonclassical (nonrigid) rotational inertia (NCRI 18 ) has revived an intense interest 20,21,22,23,24 in the existence and properties of the supersolid phase in this system, as well as in the possible emergence of exotic phases in other systems.…”
Section: B Nonclassical (Non-rigid) Rotational Inertiamentioning
confidence: 99%
See 1 more Smart Citation
“…The existence of an exotic supersolid crystalline phase with combined solid and superfluid characteristics has been long conjectured 16,17,18 for solid 4 He under appropriate conditions. The recent experimental discovery 19 that solid 4 He exhibits a nonclassical (nonrigid) rotational inertia (NCRI 18 ) has revived an intense interest 20,21,22,23,24 in the existence and properties of the supersolid phase in this system, as well as in the possible emergence of exotic phases in other systems.…”
Section: B Nonclassical (Non-rigid) Rotational Inertiamentioning
confidence: 99%
“…In the context of the appearance of supersolid behavior of 4 He under appropriate conditions, formation of a supersolid fraction is often discussed in conjunction with the presence of (i) real defects and (ii) real vacancies. 16,17 Our REM wave function [Eq. 2] belongs to a third possibility, namely to virtual defects and vacancies, with the number of particles equal to the number of lattice sites (in the context of 4 He, the possibility of a supersolid with equal number of particles and lattice sites is mentioned in Ref.…”
Section: Lmmentioning
confidence: 99%
“…This shift was interpreted as due to mass decoupling from the oscillator and it was suggested that this was likely evidence for a supersolid phase of solid 4 He that was first predicted many years earlier [4][5][6][7]. This interpretation of the presence of non-classical rotational inertia (NCRI) continues to be controversial, but has spawned considerable experimental and theoretical activity [8].…”
mentioning
confidence: 99%
“…The above conclusions were based on the assumption of a positive coupling constant d in Eq. (2). Formally, for negative d, our conclusions would have been inverted-an expansion would enhance the local supersolid transition while a contraction would reduce the supersolid transition temperature.…”
Section: Discussionmentioning
confidence: 99%